Evaluation of Antimicrobial Effect of Herbal Medicaments - Mangosteen, Turmeric, Babul Extracts, and Chlorhexidine against Candida albicans Biofilm in Endodontics: An In Vitro Study - Vinoo Subramaniam Ramachandran; Mensudar Rathakrishnan; Vidya Kazhiyur Mudimbaimannar; Malathy Balaraman Ravindrran; Alargarsamy Venkatesh; Jayakumar Dinakar (Wolters Kluwer Medknow Publications, 2023)
Introduction: Identification of causative microorganisms in the infected root canal can help in successful treatment. Microorganisms produce a mixture of organic volatile compounds, and determining these volatile organic compound metabolites by gas chromatography/mass spectrometry (GC/MS) can help in pathogen identification in significant time by detecting the signature compounds of that particular organism. Commonly used root canal medicaments can cause a cytotoxic effect on tissue. Herbal medicaments with antimicrobial properties and less toxicity can be used as alternatives. This study aimed to evaluate in detail the metabolomes of Candida albicans and also assess the antimicrobial efficacy of herbal medicines (mangosteen, turmeric, and babul extracts) and chlorhexidine against C. albicans biofilm. Materials and methods: To examine the volatile organic compounds of C. albicans, the GC/MS method was employed. The phytochemical constituents of natural medicament extracts were identified using GC-MS analysis. Ethanol extracts of medicaments (50 mg/mL) were prepared and agar well diffusion method was used to assess the antimicrobial activity of herbal medicaments. Group 1: mangosteen extract, Group 2: babul extract, Group 3: turmeric extract, Group 4: chlorhexidine, Group 5: saline with chlorhexidine as a positive control. Results: Volatile organic compound metabolites determined by GC/MS revealed the signature volatile compounds of C. albicans. Antimicrobial evaluation by agar-well diffusion assay showed that babul exhibited the lowest zone of inhibition, whereas 2% chlorhexidine showed the highest zone of inhibition, followed by mangosteen extract. Conclusion: Due to their relative biosafety, natural plant-derived root canal medicaments can be considered as alternative options compared to synthetic medicaments.